Integrating technology for Construction Site Safety Management (CSSM) in Pakistan: challenges and ways forward - Samiullah, Sohu; Md Kassim, Tahara Ramadzan (Penerbit UTHM, 2025)
Construction in Pakistan remains one of the most hazardous sectors globally, with persistent safety lapses and slow adoption of modern technologies. This study investigates the obstacles preventing effective integration of technology into Construction Site Safety Management (CSSM). Despite global progress in CSSM technologies like IoT, BIM, AR/VR, and AI, Pakistani construction sites largely depend on manual safety practices. This results in low efficiency and increased workplace hazards. The primary objective is to identify and major barriers to integrating technology in CSSM within Pakistan and propose practical, context-sensitive solutions for advancing safety protocols. Adopting a sequential explanatory design, the research began with a quantitative survey of Pakistani construction professionals to rank challenges in technology adoption. Following the survey, qualitative interviews were conducted with industry experts to delve deeper into these barriers and explore feasible solutions. Quantitative insights helped shape the qualitative discussions, leading to evidence-based recommendations. The results of the study identified key challenges to technology integration in CSSM, including costly setups, financial limitations, and a significant gap in research and development. Experts suggests potential solutions such as establishing public-private partnerships, initiating modular technological implementations, and setting up dedicated research centers to address these challenges. This finding provide effective recommendations for stakeholders in Pakistan’s construction industry to enhance safety practices through the strategic integration of technology. The proposed solutions offer a roadmap for overcoming financial and research-related challenges, thereby improving occupational safety standards mainly in the construction industry.